Analysis of Segmental Mobility Following a Novel Posterior Apical Short-Segment Correction for Adolescent Idiopathic Scoliosis - Hosseini, Pooria; Nnadi, Colin; Rehák, Ľuboš; Repko, Martin; Grevitt, Michael; Aydinli, Ufuk; Carl, Allen; Pawelek, Jeff; Crandall, Dennis; Akbarnia, Behrooz A (Spine, 2016)
STUDY DESIGN: A prospective, nonrandomized, multicenter study. OBJECTIVES: The purpose of this study was to evaluate the amount of motion present at instrumented but unfused segments and at motion segments adjacent to the instrumentation following application of a new posterior apical short-segment correction technique for correcting adolescent idiopathic scoliosis (AIS). SUMMARY OF BACKGROUND DATA: High-density pedicle screw instrumentation and posterior arthrodesis of all instrumented levels is the most common surgical treatment for AIS stabilization. The consequence of long fusion is an abnormal load on adjacent levels with an increased risk of future adjacent segment degeneration. METHODS: This new system applied translational and derotational forces over a short apical segment. The short apical region was prepared for fusion while maintaining motion of unfused vertebral segments. Radiographic data were collected pre-operatively, at surgery, and at 3, 6, and 12 months after surgery. RESULTS: Twenty-one female patients, mean age of 14.2 years (10.6-16.9 years) with Lenke 1A/1B curves, were enrolled. The range of motion in the unfused instrumented segment was significantly higher than the apical fused segment (11 vs. 0.9, P < 0.001). The range of motion of unfused vertebral levels distal to the construct at one year did not differ significantly from their respective pre-op values. When the analysis was extended to understand the impact of lower instrumented vertebra (LIV) on motion of unfused segments distal to the construct, it appeared that (1) the change in motion from pre-op to 12 months post-op as a function of LIV is not statistically significant; and (2) The motion of the unfused distal vertebral segments at 12 months does not statistically increase with a lower LIV. CONCLUSION: Through one year, this novel technique achieved and maintained similar AIS correction to current posterior fusion techniques while maintaining the mobility of unfused motion segments with less implant density. LEVEL OF EVIDENCE: 4.
Keywords: skolióza; Retrospective Studies; mladiství; Radiography; výsledek terapie; pedikulární šrouby; Prospective Studies; dítě; Thoracic Vertebrae; Child; ženské pohlaví; radiografie; retrospektivní studie; prospektivní studie; Humans; Scoliosis; fúze páteře; Spinal Fusion; Pedicle Screws; hrudní obratle; rozsah kloubních pohybů; Female; Adolescent; Treatment Outcome; Range of Motion, Articular; lidé